1977
DOI: 10.1073/pnas.74.9.3767
|View full text |Cite
|
Sign up to set email alerts
|

3-Nitropropionate, the toxic substance of Indigofera , is a suicide inactivator of succinate dehydrogenase

Abstract: We have shown that 3-nitropropionate, an isoelectronic analogue of succinate, is a suicide inactivator of succinate dehydrogenase [succinate:(acceptor) However, the precise mechanism of inactivation, as well as mechanistic extrapolations to the oxidation of succinate, must await the elucidation of the structure of the modified enzyme. We can now explain the toxicity of plants such as Indigofera endecaphylla for mammals and fowl as being due to the irreversible blockage of the Krebs cycle by 3-nitropropionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
202
1
8

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(217 citation statements)
references
References 22 publications
6
202
1
8
Order By: Relevance
“…This approach has been widely used in previous studies of both in vitro and in vivo subjects to generate an experimental model of mitochondrial dysfunction (Alston et al, 1977;Coles et al, 1979;Ludolph et al, 1992). Studies have shown that the resulting level of ATP suppression following a 3-NP treatment is dose-and timedependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach has been widely used in previous studies of both in vitro and in vivo subjects to generate an experimental model of mitochondrial dysfunction (Alston et al, 1977;Coles et al, 1979;Ludolph et al, 1992). Studies have shown that the resulting level of ATP suppression following a 3-NP treatment is dose-and timedependent.…”
Section: Discussionmentioning
confidence: 99%
“…However, whether the mitochondrial energy production is a crucial factor that controls the cell's decision to die by apoptosis or necrosis is not known, nor is the role of mitochondrial energy production in regulating the apoptotic process, once the process is initiated. To address these issues, we used an established model of mitochondrial dysfunction induced by local application of 3-nitropropionic acid (3-NP), an irreversible inhibitor of succinate dehydrogenase (SDH), to produce mitochondrial dysfunction (Alston et al, 1977;Coles et al, 1979;Ludolph et al, 1992), and investigated the effects of the mitochondrial energetic deficiency on the generation of apoptosis and necrosis following exposure to intense noise. Specifically, the following questions were addressed: In the noise-damaged cochlea, did reduction of the mitochondrial energy production: (1) prevent the induction of apoptosis; (2) shift OHC death from apoptosis to necrosis; (3) disrupt the execution of the apoptotic process?…”
Section: Introductionmentioning
confidence: 99%
“…First, calcium influx may initially stimulate mitochondrial respiration (Hansford, 1985;McCormack et al, 1990;Li et al, 1996). As a suicide inhibitor, 3-NP inactivates SDH more rapidly when the enzyme activity is higher (Alston et al, 1977). Second, calcium and sodium influx may stimulate the consumption of ATP through Ca 2ϩ -ATPase and Na ϩ /K ϩ -ATPase.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, however, NMDA receptor antagonists attenuated but did not prevent neuronal death, suggesting that there is an NMDA-independent mechanism (Weller and Paul, 1993;Fink et al, 1996). Recently, Behrens and colleagues (1995) reported that 3-nitropropionic acid (3-NP), a suicide inhibitor of the mitochondrial enzyme succinate dehydrogenase (SDH) (Alston et al, 1977), induced apoptosis in neuronal cultures and that excitotoxicity was not involved.…”
mentioning
confidence: 99%
“…Labeling of aspartate, glutamate, and glutamine from [1-14 C]pyruvate therefore reflects pyruvate carboxylation. We used 3-nitropropionic acid to block the TCA cycle at the level of succinate dehydrogenase (Alston et al, 1977), leaving pyruvate carboxylation the only route for 14 C to enter the TCA cycle (Fig. 1) (Hassel et al, 1992(Hassel et al, , 1997Waniewski and Martin, 1998) to determine whether pyruvate carboxylation occurs in neurons in vivo.…”
mentioning
confidence: 99%